Support of student youth’s mental health - Radchuk, Naum; Kryzhanovska, Zoreslava (Lesya Ukrainka Volyn National University, 2022)
This scientific research is a continuation of a series of studies in various fields of scientific knowledge devoted to the study of the mental health’ issue. We aim to pay attention to the issue of youth mental health support and increase public awareness of it.
Keywords: student youth; crisis; family environment; emotional state; mental disorders